2015
DOI: 10.4103/1735-1995.170622
|View full text |Cite
|
Sign up to set email alerts
|

Uterine and arcuate arteries blood flow for predicting of ongoing pregnancy in in vitro fertilization

Abstract: Background:In this study, we aimed to investigate the ability of transvaginal Doppler ultrasonography in predicting in vitro fertilization (IVF) outcome in women undergoing this procedure.Materials and Methods:In this prospective observational study, 65 infertile women underwent IVF procedure in Isfahan, during 2013-2014, were studied. The pulsatility index (PI), resistive index (RI) and peak systolic velocity (PSV) of the uterine arteries and arcuate arteries were measured in all selected women using transvag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 18 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Two other studies linked implantation failure in IVF cycles with a decrease (28) or lack (29) of blood flow in the subendometrium. Furthermore, it has been represented that women with a successful IVF procedure had lower PI and RI of uterine and arcuate arteries compared to those with an unsuccessful IVF (30). Similarly, Yalti et al (31) found that women who conceived with intrauterine insemination had a lower uterine artery PI compared with those who did not conceive at all.…”
Section: Discussionmentioning
confidence: 99%
“…Two other studies linked implantation failure in IVF cycles with a decrease (28) or lack (29) of blood flow in the subendometrium. Furthermore, it has been represented that women with a successful IVF procedure had lower PI and RI of uterine and arcuate arteries compared to those with an unsuccessful IVF (30). Similarly, Yalti et al (31) found that women who conceived with intrauterine insemination had a lower uterine artery PI compared with those who did not conceive at all.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement encompassed the thickest echogenic area from one stratum basalis endometrial interface to the other [35]. Additionally, the pulsatility index (PI) and resistive index (RI) of the uterine arteries at the cervical-corporeal level of the uterus were recorded [36]. If the EM pattern was trilaminar and the EM thickness was below 7 mm, autologous PRP treatment was offered after obtaining informed consent.…”
Section: Endometrial Preparation and Euploid Frozen-thaw Embryo Trans...mentioning
confidence: 99%